Pengaruh Halal Label dan Brand Image Terhadap Purchase Decision Melalui Consumer Trust Pada Restoran Cepat Saji Lokal - Farhan Adam Ramadhan; Andi Hidayat Muhmin (Economic Reviews Journal, 2025)
The rapid development of local fast-food restaurants has intensified competition among business players, making halal labels and brand image essential factors that influence purchase decisions through consumer trust. This study aims to analyze the effect of halal labels and brand image on purchase decisions, as well as the mediating role of consumer trust. The population of this study consists of Gacoan restaurant consumers residing in the Greater Jakarta area (Jabodetabek). A total of 130 respondents were selected using purposive sampling based on criteria of being 17–28 years old, having consumed Gacoan products, and having purchased them at least three times in the last six months. Data were collected through an online questionnaire using a 5-point Likert scale. Instrument validity and reliability were tested using SPSS, while hypothesis testing was conducted using the SEM PLS method with SmartPLS4 software. The results show that halal labels positively affect consumer trust and purchase decisions, brand image positively affects consumer trust and purchase decisions, and consumer trust positively affects purchase decisions. Moreover, consumer trust is proven to mediate the influence of halal labels and brand image on purchase decisions. These findings confirm that halal labels and brand image play a strategic role in building consumer trust, which ultimately encourages purchase decisions.